Pemanfaatan Pupuk Hijau Daun Lamtoro (Leucaena leucocephola) dan Pupuk Organik Cair Bonggol Pisang Terhadap Pertumbuhan dan Produksi Tanaman kacang Panjang (Vigna sinensis L) - Muhammad Agus Irwanda; Gusmeizal Gusmeizal; Abdul Rahman (Jurnal Ilmiah Pertanian ( JIPERTA), 2022)
Utilization of Lamtoro Leaf Green Manure (Leucaena Leucocephala) and Banana Weevil Liquid Organic Fertilizer on Growth and Production of Long Beans (Vigna Sinensis L). Under the guidance of Mr. Ir.H.Gusmiezal,MP as chairman and Mr. Ir .H.Abdul Rahman, MS as a member. The study was conducted in the experimental garden of the Faculty of Agriculture, University of Medan Area. Percut Sei Tuan District, Deli Serdang Regency, North Sumatra in July-October 2021. The study used a factorial randomized block design (RAK), with 2 (2) treatment factors, namely; the first is (1) the factor of giving lamtoro leaf green manure with 4 (4) levels of treatment, namely; L0 = without treatment (control) L1 = dose of 10 tons/ha (1.44 kg/plot) L2 = dose of 20 tons/ha (2.88 kg/plot) L3 = dose of 30 tons/ha (4, 32 kg/ha)The second (2) factor for giving liquid organic green Pupuh Banana weevil, namely; P0 = without organic fertilizer (control) P1 = application of organic fertilizer with a concentration of 5% P2 = application of organic fertilizer with a concentration of 10% P3 = application of organic fertilizer with a concentration of 15%. Parameters observed were: Plant height (cm), Stem diameter (cm). Flowering age (days). Production per plant (g). Production per plot (kg). The results showed that the green manure of lamtoro leaves showed significant results in the L3 treatment with a dose of 30 tons/ha (4.32 kg/plot) and for the application of liquid organic fertilizer the Banana Bonggol gave significant results in the P3 treatment with a concentration of 15%. For the combination of the 2 treatments, the real treatment was L1P3 (Lamtoro application with Banana weevil POC).